KARAKTERISASI REKAHAN ALAMI BATUAN DASAR LAPANGAN PONDOKMAKMUR, CEKUNGAN JAWA BARAT UTARA - P Fortraniawan, R
Basement fractured reservoir is one type of natural fractured reservoir rock that has great potential to be explored in the search for hydrocarbons. Most of the natural reservoir including reservoir fractured of bedrock was discovered by accident (Aguilera, 1995). Natural fractured reservoir are more complicated and expensive to be explored compared with other types of reservoirs (Nelson, 2001). In general, this geological model, often found in areas strongly affected by tectonic compression process because the rock will faulted and folded, particularly in rocks that are rigid, as in the basement, the tectonic processes will lead to a lot of cracks and fissures that a reservoir of potential models, especially on the model of the conductive fracture (open fracture). The research area is located in Kecamatan Cabangbungin, Kabupaten Bekasi, Jawa Barat. This study aims to characterize natural fractures then determine and analyze the patterns of structure and tectonic regime of the research area and its influence on the pattern and intensity of natural fractures that form on the research area. While the data used in this study are drilling well data, three-dimensional seismik, and log image of the existing drilling wells in this field. Knowledge of the distribution and pattern of conductive fractures in basement is one way to increase production of oil and gas. The results shows that pattern of natural fractures (conductive and resistive) tend to the North-South direction and East-West. The pattern may be more influenced by Eocene- Oligocen tectonics period. While the North West - South East pattern predicted are the effect of Java tectonics pattern Oligocene to Present period. The most highly conductive fracture intensity in the depth of the wells are close to faul